Hydroalkylation of Unactivated Alkenes with Ketones and 5-Benzylfurfurals Enabled by Amine/Pd(II) Cooperative Catalysis - Sayed, Mostafa; Shen, Hong-Cheng; Zhang, Ling; Gong, Liu-Zhu (Synthesis, 2020)
An intermolecular addition of ketones to unactivated alkenes has been developed by means of Pd(II)/amine cooperative catalysis, which incorporates the simultaneous activation of amide-containing alkenes and α-carbon of ketones enabled by Pd(II) catalyst and enamine, respectively. Moreover, the addition of 5-benzylfurfural derivatives to an unactivated alkene has also been achieved by integrating Pd(II) and trienamine catalysis to provide γ-adducts at the benzylic position of furfurals in good to high yields.
Keywords: alkene; ketones; 5-benzylfurfurals; hydroalkylation; cooperative catalysis